Capturing differential diffusion effects in large eddy simulation of turbulent premixed flames - Yao, Matthew X.; Blanquart, Guillaume (Proceedings of the Combustion Institute, 2024)
The combustion of hydrogen in low-swirl burners (LSB) is considered as an alternative means of generating power because it is characterized by low emissions and high efficiency. However, lean hydrogen premixed flames are subject to thermodiffusive instabilities induced by the large diffusivity, and hence small Lewis number, of hydrogen. The numerical modelling of these flows remains challenging because the transition of small scale instabilities into large scale turbulent structures cannot be modelled by conventional strategies. Recently, Schlup and Blanquart (2019) developed a two-equation model which captures successfully the phenomena arising from differential diffusion and curvature effects. The chemistry tabulation framework is based on the classical progress variable approach and introduces an additional transport equation to account for fluctuations in the local equivalence ratio due to these effects. In the current work, this model is extended to large eddy simulation (LES) of an LSB. The LES model is applied first to a CH4/air flame (ϕ=0.59) to validate the overall simulation framework and then to a H2/air flame (ϕ=0.4). The results obtained with this new formulation show significant improvement over the traditional one-equation formulation. The unique flow field exhibited by lean hydrogen is reproduced successfully using the two-equation model.